Localization and delocalization of deformation in a bimineralic material. Issue 5 (13th May 2015) - Jammes, Suzon; Lavier, Luc L.; Reber, Jacqueline E.
Abstract We investigate how localization and delocalization of deformation occurs in a bimineralic material composed of a strong plagioclase and a weaker quartz phase. We perform numerical, meter‐scale shear experiments in which we vary the temperature and the ratio of the two mineral phases. Three micromechanical deformation fields are identified according to the mechanical behavior of the minerals at play (brittle or ductile when both phases are in the brittle or ductile regime, respectively, and semibrittle when one phase is in the brittle and the other in the ductile regime). Besides these micromechanical deformation fields, we identify three deformation types characterizing the degree of localization (type I: localized shear zone, type II: localized anastomosing shear zone, and type III: delocalized shear zone). Type I is expected in the brittle deformation field. In the semibrittle field, all deformation types can be observed depending on the amount of weak phase present. In the ductile field, deformation is dependent on the strength ratio between the two phases. For a low strength ratio, deformation of type III is always observed. For high‐strength ratios, deformation of type II can be observed for a moderate amount of weak phase. A small amount of weak phase (<10%) reverses the mechanical behavior of the strong phase and leads to the formation of a narrow anastomosing shear zone (type II) where fully ductile (type III) behavior is expected. This highlights the importance of a bimineralic material for the deformation localization and overall large‐scale deformation processes.